Anthropometric and physical fitness parameters versus specific performance tests in Brazilian field hockey athletes: a pilot study - Lemos Raquel Silva; Paz Gabriel Andrade; Freitas Maia Marianna de; Baptista da Silva Jurandir; Lima Vicente Pinheiro; Brandão Pinto de Castro Juliana; Miranda Humberto (Sciendo, 2017)
Study aim: To investigate the correlation between anthropometric parameters, Sargent jump test, core muscles endurance and agility performance versus specific tests with and without a ball in female Brazilian field hockey athletes.